Ozone Exposure Controls Oxidative Stress and the Inflammatory Process of Hepatocytes in Murine Models - Silvania Mol Pelinsari; Mariáurea Matias Sarandy; Emerson Ferreira Vilela; Rômulo Dias Novaes; Jade Schlamb; Reggiani Vilela Gonçalves (Antioxidants, 2024)
(1) Background: Ozone exposure is a promising tool for treating liver damage since it is known to control the release of free radicals and increase the expression of antioxidant enzymes. The objective is to investigate the main intracellular pathways activated after exposure to ozone, considering the dosage of antioxidant enzymes and markers of oxidative stress. (2) Methods: This systematic review was performed based on the PRISMA guidelines and using a structured search in MEDLINE (PubMed), Scopus, and Web of Science. Bias analysis and methodological quality assessments were examined using the SYRCLE Risk of Bias tool. (3) Results: Nineteen studies were selected. The results showed that the exposure to ozone has a protective effect on liver tissue, promoting a decrease in inflammatory markers and a reduction in oxidative stress in liver tissue. In addition, ozone exposure also promoted an increase in antioxidant enzymes. The morphological consequences of controlling these intracellular pathways were reducing the tissue inflammatory process and reducing areas of degeneration and necrosis. (4) Conclusions: Ozone exposure has a beneficial effect on models of liver injury through the decrease in oxidative stress in tissue and inflammatory markers. In addition, it regulates the Nrf2/ARE antioxidant pathway and blocks the NF-κB inflammatory pathway.